THE MOST DANGEROUS ANIMAL OF ALL : SEARCHING FOR MY FATHER ... AND FINDING THE ZODIAC KILLER - STEWART, GARY L. (HARPER, 2014)
A thirty-nine-year-old adoptee describes his discovery that his birthfather is one of the most infamous and still-wanted serial killers in American history, forcing him to reconsider everything he thought he knew about himself.